Cognitive sciences: a challenge whithin the social sciences environment - de Castro Aguirre, Constancio (Huarte de San Juan. Geografía e Historia, 2013)
The present work goes into the traditional philosophical field, the knowledge theory. A brilliant exposer of this tradition, Ernst Cassirer, and his personal contribution introducing the active role of symbolic system is presented. The cognitive vocabulary is changing towards a new empirical sciences perspective. One of the active behavioral science promoter such as Herbert Simon and his Science of the Artificial is kept in memory because of its analogy to Cassirers position. Building cognitive sciences is acomplished through the several social sciences contacts performing a real interdisciplinary research. The researchers such as Jerome Bruner, Roger Brown and George A. Miller and the presence of Foundations supporting finances all of them are carefully reported. Finally the cognitive sciences come into the teaching programs across the numerous and prestigious universities in the world.
Keywords: Symbolic univers; Science of the Artificial; transversal interdisciplinary reesearch